Atrial fibrillation in the young: clinical characteristics, predictors of new onset and outcomes. (24th May 2021) - Segev, A; Maor, E; Goldenfeld, M; Grossman, E; Beinart, R; Klempfner, R; Sabbag, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Atrial fibrillation (AF) onset in the young (≤45 years) is uncommon and not well studied. Purpose: Identifying the determinants of AF in this population in order to help direct timely diagnosis, appropriate follow up and management. Methods: We retrospectively evaluated all patients aged ≤45, admitted to the internal and cardiology wards between January 2009 and December 2019 at a large tertiary center. Clinical, electrocardiographic and echocardiographic data were collected and compared among patients with and without AF at baseline. A subgroup of patients with no AF at baseline and a subsequent hospital visit were followed for development of new onset AF (NOAF). Results: A total of 16, 432 patients (55.5% male, 33 ±8.3 years old) were analyzed. At baseline, patients with AF (n = 366) tended to be older, more often male, and had a higher proportion of comorbidities and ECG conduction disorders, compared with the patients without AF (n = 16, 066). Male sex, increased age, obesity, heart failure (HF) and the presence of left or right bundle branch block (LBBB and RBBB, respectively) were all strongly and independently associated with young-onset AF. A total of 10, 691 patients were followed for a median of 41.5 (16.6-78.6) months, during which 85 patients developed NOAF (equivalent to 0.5%/year). Increased age, hypertension, HF, RBBB and LBBB were independent predictors of NOAF. CHARGE-AF score outperformed CHA2DS2-VASc score in NOAF prediction [AUC of ROC 0.75 (0.7-0.8) vs. 0.56 (0.48-0.65)]. Conclusions: The annual risk of NOAF among young adults admitted to the hospital is noteworthy. NOAF may be predicted by clinical risk factors and the CHARGE-AF score.